2018
DOI: 10.3390/su10030586
|View full text |Cite
|
Sign up to set email alerts
|

Curve Number Applications for Restoration the Zarqa River Basin

Abstract: The great demand for water resources from the Zarqa River Basin (ZRB) has resulted in a base-flow reduction of the River from 5 m 3 /s to less than 1 m 3 /s. This paper aims to predict Curve Numbers (CNs) as a baseline scenario and propose restoration scenarios for the ZRB. The method includes classifying the soil type and land use, predicting CNs, and proposing CN restoration scenarios. The prediction of existing CNs will be in parallel with the runoff prediction by using the US Army Corps of Engineers HEC-1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The reservoir of KTD receives runoff from the basin and wastewater from treatment plants, i.e. the flow of the Zarqa River mixed with treated effluents from WWTPs and is finally stored in King Talal Dam, where the dam's water is used for irrigation in the Jordan valley [Al-Taani et al 2018; Shammout et al 2018]. The reservoir also control water releases to the central part of the Jordan valley where it is mixed with the canal water diverting water from upstream sources.…”
Section: Methodology Study Site and Industriesmentioning
confidence: 99%
“…The reservoir of KTD receives runoff from the basin and wastewater from treatment plants, i.e. the flow of the Zarqa River mixed with treated effluents from WWTPs and is finally stored in King Talal Dam, where the dam's water is used for irrigation in the Jordan valley [Al-Taani et al 2018; Shammout et al 2018]. The reservoir also control water releases to the central part of the Jordan valley where it is mixed with the canal water diverting water from upstream sources.…”
Section: Methodology Study Site and Industriesmentioning
confidence: 99%
“…Focusing on dimensions around the world, changes in land use, particularly urbanization are currently on the schedule of policy-makers to provide tools and policies Urbanization mainly happened on expenses of rangelands and rain-fed vegetables and crops areas, as well as the expansion of irrigated areas, also on expenses of rangelands. These trends of land use/cover changes, particularly the urban areas with a high percentage of change at 3.01%, have added further pressure on water supply and led to the overpumping of groundwater to balance inhabitants demand in the Yarmouk Basin [7,10]. Findings of [50,51] showed that need for water has risen with urbanization and land uses.…”
Section: Analysis Of Land Use/cover Changes Of the Yarmouk River Basinmentioning
confidence: 99%
“…The relationship between water resources management and land use/cover is highly relevant, inextricably entwined, and the need to protect the quantity and quality of water resources can influence potential land uses and land management practices [7,8]. Although this relationship is complex with respect to surface basins and groundwater recharge due to diversity with topography, as well as hydrogeological characteristics [9], water-makers, from governments to nonprofits to corporations, often manage water resources and land use for multiple uses [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, the purpose of NRCS method was to obtain runoff estimates for agricultural watersheds from storm rainfall events in the USA 5 . However, due to its convenience, water resources practitioners have adopted its usage in multiple regions and land uses 6 – 13 . In addition to its application in rainfall-runoff modelling, the NRCS-CN method has been successfully applied in urban hydrology 14 – 16 , water quality 17 19 , rainwater harvesting 3 , 20 22 , subsurface flow estimation 23 26 , and estimation of evapotranspiration (ET) 27 – 29 .…”
Section: Background and Summarymentioning
confidence: 99%